Teacher Upgrading Skill in Preparing Materials and Examination Based on Images in Sibolga City - Andriayani, Andriayani; Zuhra, Cut Fatimah; Maghfirah, Awan; Yanti, Maulida; Gea, Saharman; Pasaribu, Khatarina Meldawati; Piliang, Averrous Fazlurrahman (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
There are 61 primary/ibtidaiyah schools, 18 junior high schools, and 18 senior high schools in the city of Sibolga, which is located in Teluk Tapian Nauli, with a total number of teachers of about 2000. This is in line with the vision of Sibolga city (2016-2021) in order to create a stable, advanced, and successful Sibolga City by producing highly competitive quality human beings in order to create a harmonious, peaceful, secure and unified society. As mentioned above, one of its mission points is to prepare human resources (HR) that have integrity, reliable, competitive, expert in science and technology so that they able to compete in the global job market. As the education stakeholder, Sibolga Education and Culture Official has plan many outstanding work programs such as made a collaboration in partnership with the Universitas Sumatera Utara community service team. As a result, based on field observations and discussions, it was known that one of the obstacle that facing by the teachers in Sibolga is not being able to provide teaching materials and also picture-based examination questions as contained in the question grid. Currently, there are several technology-driven applications that can be used to make images or graphics creating process easier. Two of them are, GeoGebra Classic that used to create graphics and images in mathematics and Chemdraw that used to create structure images that related to chemistry. In addition word optimization training was also conducted to optimize teacher on preparing teaching materials with Ms. word.